2002
DOI: 10.1093/humrep/17.9.2464
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic diagnosis: patients' experiences and attitudes

Abstract: The experience of prenatal diagnosis and termination of pregnancy can be an unwelcome memory and this leads to a demand for an alternative approach. Our data suggest that PGD is acceptable to patients and is a valuable alternative to prenatal diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
87
3
9

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 19 publications
4
87
3
9
Order By: Relevance
“…PGD for hereditary cancer is particularly controversial and is still not widely used. [4][5][6][7] Lavery et al 8 found that PGD users (for diseases other than FAP) and who also had experience with PND reported that the experience of PND followed by termination had a negative impact and that PGD is a potentially valuable alternative. Although the first PGD procedures for FAP were already performed in 1998, 3 the availability of both PND and PGD for FAP still varies between countries.…”
Section: Introductionmentioning
confidence: 99%
“…PGD for hereditary cancer is particularly controversial and is still not widely used. [4][5][6][7] Lavery et al 8 found that PGD users (for diseases other than FAP) and who also had experience with PND reported that the experience of PND followed by termination had a negative impact and that PGD is a potentially valuable alternative. Although the first PGD procedures for FAP were already performed in 1998, 3 the availability of both PND and PGD for FAP still varies between countries.…”
Section: Introductionmentioning
confidence: 99%
“…114 According to the study, PGD was acceptable to most patients and offered a valuable alternative to PND, but undergoing IVF itself was associated with stress and anxiety: 41% of patients found the PGD cycle extremely stressful, especially the time waiting after embryo transfer for a pregnancy result and time waiting after the initial consultation before a treatment cycle. The patients regarded as the main advantage of PGD that only unaffected embryos were transferred to the uterus and thus therapeutic termination could be avoided.…”
mentioning
confidence: 98%
“…114 Counselling has been noted to provide help in areas of psychological assistance, technical explanations and discussing relationships. 136 At best, genetic counsellors are sensitive also for the burden of an infertility diagnosis and the emotional impact -including anxiety and ethical questions -of different treatment options.…”
mentioning
confidence: 99%
“…This preference has been observed before in couples with different genetic disorders, including cancer susceptibility syndromes as hereditary breast and ovarian cancer and familial adenomatous polyposis syndrome. [19][20][21][22][23] In a recent study among couples with a broad spectrum of genetic disorders, 74% of couples preferred PGD over PND for diagnostic testing in a future pregnancy. 24 The preference for PGD can partly be explained by the fact that PGD offers patients the possibility to have an unaffected genetically related child while termination of a pregnancy can be avoided.…”
Section: Discussionmentioning
confidence: 99%